Sensitivity to Functional Improvements of Gmfm-88, Gmfm-66, and Pedi Mobility Scores in Young Children with Cerebral Palsy. Issue 1 (August 2014) - Ko, Jooyeon
This study assessed the sensitivity to functional change of the total score on age- and severity-relevant dimensions (Goal Total score) of the Gross Motor Function Measure (GMFM)-88 compared with GMFM-88 Total, GMFM-66, and Pediatric Evaluation of Disability Inventory (PEDI) Mobility scores in children with cerebral palsy (CP). Correlations among the four parameters were calculated to assess how sensitivity may differ according to the severity of CP. 64 children with CP ( M age=43.8 mo., SD =16.5, range=21 to 84 mo.; 36 boys, 28 girls) were recruited. The GMFM and PEDI assessments were performed over an interval of 6 mo. The effect sizes for changes over time were large (0.88 to 1.26) for the selected GMFM-88 Goal Total scores. The minimally important differences of the GMFM-88 Goal Total scores were within the mean range of change, with CP severity categorized as GMFCS Levels I/II, Level III, and Levels IV/V. The selected GMFM-88 Goal Total scores showed from poor to good correlations with GMFM-88 Total, GMFM-66, and PEDI Mobility scores. The results indicated that age- and severity-relevant GMFM-88 Goal Total scores were the optimal parameter to detect meaningful change in children with CP for clinical and research use.